Efektifitas Metode Belajar Sambil Bermain Dalam Pembelajaran Matematika DI SD Negeri 3 Joton - Isnaeni Nur Ladzuni; Celsi Julia Andini; Theresia winda Setyaningrum; Nela Rofisian (Journal Educational Research and Development | E-ISSN : 3063-9158, 2024)
Mathematics is a subject that is often a scary specter. Students generally assume that this subject is difficult to understand, monotonous, contains too many formulas, and has minimal application in real-life contexts. In this case, teachers have an important task in designing mathematics learning activities so that they can be interesting and popular with students. Educational strategies that combine mathematics learning with play activities are aimed at fostering students' interest in learning. The data collection method used is literature study. Using secondary data sources in the form of research results such as articles, journals, books and other relevant sources. The data analysis techniques used in this study are data analysis and content analysis techniques. The results of the literature review found the benefits of play methods in learning and examples of play methods in mathematics learning.